Topological estimation of aerodynamic controlled airplane system functionality of quality - Павлова, С.В. (Proceedings of National Aviation University (archive), 2005)
It is suggested to use topological methods for stage estimation of aerodynamic airplane control in widespread range of its conditions The estimation is based on normalized stage virtual non-isotropy of configurational airplane systems calculation.